Effect of five different stages of ripening on chemical compounds in medlar (Mespilus germanica L.) - Rop, Otakar; Sochor, Jiri; Jurikova, Tunde; Zitka, Ondrej; Skutkova, Helena; Mlcek, Jiri; Salas, Petr; Krska, Boris; Babula, Petr; Adam, Vojtech; Kramarova, Daniela; Beklova, Miroslava; et al. (Molecules (Basel, Switzerland), 2010)
The study of changes of nutritional value of fruit during the ripening process can help estimate the optimal date for fruit harvesting to achieve the best quality for direct consumption and further utilization. The aim of this study was to monitor the changes of chemical composition of medlar fruit (Mespilus germanica L.) measured at five various ripening stages including 134, 144, 154, 164 and 174 days after full bloom (DAFB). Fruits were analyzed and ascorbic acid (AA) and total phenolic compound content with respect to the total antioxidant activity were determined. In addition, selected micronutrients and macronutrients were monitored. The results of our experiments demonstrate that ascorbic acid, total phenolic compound content and total antioxidant activity decreased significantly with increasing time of ripeness. The decreasing tendency in potassium, calcium and magnesium contents during the ripening stages was also determined. During the ripening period, the content of all micronutrients as well as phosphorus and sodium was balanced, with no statistically significant differences between the monitored ripening stages, which can be considered as a positive fact with respect to ideal consumption quality of fruit.
Keywords: Chromatography, High Pressure Liquid; antioxidancia; Spectrophotometry, Ultraviolet; Phenols; Antioxidants; Rosaceae; fenoly; spektrofotometrie ultrafialová; vysokoúčinná kapalinová chromatografie